Evaluation of engine performance and emissions using blends of gasoline, ethanol, and fusel oil - S. M., Rosdi; Erdiwansyah, .; Mohd Fairusham, Ghazali; Rizalman, Mamat (Elsevier Ltd, 2025)
This study investigates the impact of gasoline, ethanol, and fusel oil blends on engine performance and emissions under varying engine speeds (1000–3000 rpm) and throttle positions (10–40 %). The blends reduced brake power by 3.5–7.1 % and increased Brake-Specific Fuel Consumption by 6.1–16.8 % for ethanol and 4.6–15.9 % for fusel oil. Brake thermal efficiency also declined for both blends. However, emissions improved significantly, with NOx reductions of 17.3 % (ethanol) and 13.8 % (fusel oil), CO reductions of 13.1 % and 9.1 %, and HC reductions of 8.8 % and 6.16 %, respectively. The results highlight trade-offs between performance and emission benefits.